Modes of Action of Five Different Endopectate Lyases from Erwinia chrysanthemi 3937 - Roy, Caroline (American Society for Microbiology (ASM), 1999)
Five endopectate lyases from the phytopathogenic bacterium Erwinia chrysanthemi, PelA, PelB, PelD, PelI, and PelL, were analyzed with respect to their modes of action on polymeric and oligomeric substrates (degree of polymerization, 2 to 8). On polygalacturonate, PelB showed higher reaction rates than PelD, PelI, and PelA, whereas the reaction rates for PelL were extremely low. The product progression during polygalacturonate cleavage showed a typical depolymerization profile for each enzyme and demonstrated their endolytic character. PelA, PelI, and PelL released oligogalacturonates of different sizes, whereas PelD and PelB released mostly unsaturated dimer and unsaturated trimer, respectively. Upon prolonged incubation, all enzymes degraded the primary products further, to unsaturated dimer and trimer, except for PelL, which degraded the primary products to unsaturated tetramer and pentamer in addition to unsaturated dimer and trimer. The bond cleavage frequencies on oligogalacturonates revealed differences in the modes of action of these enzymes that were commensurate with the product progression profiles. The preferential products formed from the oligogalacturonates were unsaturated dimer for PelD, unsaturated trimer for PelB, and unsaturated tetramer for PelI and PelL. For PelA, preferential products were dependent on the sizes of the oligogalacturonates. Whereas PelB and PelD displayed their highest activities on hexagalacturonate and tetragalacturonate, respectively, PelA, PelI, and PelL were most active on the octamer, the largest substrate used. The bond cleavage frequencies and reaction rates were used to estimate the number of subsites of each enzyme.